2018
DOI: 10.18639/merj.2018.04.670069
|View full text |Cite
|
Sign up to set email alerts
|

Does Climate Change Have Real Negative Impact on Economic Growth in Poor Countries? Evidence from Cote d’Ivoire (Ivory Coast)

Abstract: The objective of this paper is to determine the impact of climate change on Cote d’Ivoire’s economic performance via per capita gross domestic product (GDP) growth, change in agricultural value added, and change in the country’s cereal yield. The data ranged from 1960 to 2016. An autoregressive distributed lag (ARDL) model is used to investigate the long run dynamics between climate variables (precipitation and temperature) and the country’s per capita GDP, agricultural value added as % of GDP, and cereal yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, our findings on the negative impact of gross capital formation on agriculture and its subsectors in Ivory Coast are similar to the results of N'Zué (2018), who found that Ivory Coast's gross capital formation adversely affected the value added to agricultural products. This makes sense, especially if investments are made outside the agricultural sector to enable the processing of agricultural products (N'Zué, 2018). Under such conditions, the industrial sector's contribution to GDP will rise while agricultural value added will fall.…”
Section: Short-and Long-run Estimationsmentioning
confidence: 99%
“…However, our findings on the negative impact of gross capital formation on agriculture and its subsectors in Ivory Coast are similar to the results of N'Zué (2018), who found that Ivory Coast's gross capital formation adversely affected the value added to agricultural products. This makes sense, especially if investments are made outside the agricultural sector to enable the processing of agricultural products (N'Zué, 2018). Under such conditions, the industrial sector's contribution to GDP will rise while agricultural value added will fall.…”
Section: Short-and Long-run Estimationsmentioning
confidence: 99%
“…On the other hand, referring to the increase in cocoa production in West Africa, Steijn (2018) argues that the current pace of cocoa production is likely to slow down as cocoa trees are very sensitive to climate change and therefore, periods of drought and rainfall or excessive winds will negatively impact yields in the future. Although N'Zué (2018) argued that climate change has not yet significantly impacted the economic performance of Côte d'Ivoire and thus there was no need to worry more than necessary, some empirical studies have shown that crops (including tree crops) in many parts of the world were affected by progressive climate change, which had impacts on food supply, (Lobell et al 2008;Läderach et al 2010) as well as the ecosystems (Schroth et al 2009).…”
Section: Introductionmentioning
confidence: 99%